2018
DOI: 10.3389/fendo.2018.00592
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Change in Insulin Resistance Induced by Free Fatty Acids Is Unchanged Though Insulin Sensitivity Improves Following Endurance Exercise in PCOS

Abstract: Background: Insulin resistance (IR) is the hallmark of PCOS and it is known that exercise may decrease it. What is unknown is whether exercise may mechanistically alter the underlying IR, attenuating the dynamic lipid induced IR in insulin resistant subjects.Methods: 12 women with polycystic ovary syndrome (PCOS) and 10 age and body mass index matched controls completed an 8 week supervised exercise program at 60% maximal oxygen consumption. Before and after the exercise program, all participants underwent hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 45 publications
(55 reference statements)
2
31
0
Order By: Relevance
“…As reported previously, intralipid infusion induced insulin resistance both in control and PCOS subjects as shown by the lowering of insulin stimulated glucose disposal rates during the intralipid clamp (16). Compared to controls, the insulin stimulated glucose disposal rate showed greater suppression in PCOS (16). In our study, fetuin-A was found to be significantly higher in PCOS compared to controls, but there were no significant differences observed for FGF19, FGF21, and FGF23 between the groups.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…As reported previously, intralipid infusion induced insulin resistance both in control and PCOS subjects as shown by the lowering of insulin stimulated glucose disposal rates during the intralipid clamp (16). Compared to controls, the insulin stimulated glucose disposal rate showed greater suppression in PCOS (16). In our study, fetuin-A was found to be significantly higher in PCOS compared to controls, but there were no significant differences observed for FGF19, FGF21, and FGF23 between the groups.…”
Section: Discussionsupporting
confidence: 75%
“…We further studied the role of short-term hyperlipidemia mediated insulin resistance induced by intravenous administration of intralipid via lipid clamp and insulin administration via HIEC on plasma levels of endocrine FGFs and fetuin-A. As reported previously, intralipid infusion induced insulin resistance both in control and PCOS subjects as shown by the lowering of insulin stimulated glucose disposal rates during the intralipid clamp (16). Compared to controls, the insulin stimulated glucose disposal rate showed greater suppression in PCOS (16).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…31 Increased physical activity and weight loss improve the biochemical and phenotypic features of PCOS, thus reducing metabolic complications and thereby improving quality of life. [32][33][34] Endurance exercise intervention did not reduce weight or alter plasma MOTS-c significantly in either group; however, enhanced glucose utilization, through an improvement in IS, 35 and a reduction in IR with lower plasma glucose levels were seen following the hyperinsulinemic-euglycaemic clamp in PCOS subjects ( Table 2 and Table 4). Increasing physical activity is a therapeutic option for reducing abnormalities associated with metabolic syndrome.…”
Section: Discussionmentioning
confidence: 92%